Relasi Politik di Kabupaten Maros (Studi Pemilihan Kepala Daerah Serentak Tahun 2020 Provinsi Sulawesi Selatan) - Sumandiyar, Adi; Yahya, Muhammad; Kamaruddin, Umar; Nur, Hasruddin; Arda, Arda (Phinisi Integration Review, 2021)
This study aims to obtain in-depth interview about Political Relations in Maros Regency in the Study of Simultaneous Regional Head Elections in 2020 South Sulawesi Province. The researcher collected discourse data through electronic media, and the researcher acted as a research instrument on the political relations between the rulers and the community in the 2020 Regional Head Election contestation in Maros Regency. Sources of data are through documentation and informants, while data collection techniques are carried out through in-depth interviews which are located in Maros Regency, South Sulawesi Province. The research informants were 2 people, selected by purposive random sampling. The results showed that it developed in two dimensions, namely; subjective dimension and objective dimension. The subjective dimension is obtained through; (1) network of government actors and bureaucracy; (2) retainer network; and (3) community empowerment group networks can mobilize community support, while the subjective dimension is through creating client patrons.